“War to the knife” against thromboinflammation to protect endothelial function of COVID-19 patients - Guglielmetti, Gabriele (Crit Care, 2020)
In this viewpoint, we summarize the relevance of thromboinflammation in COVID-19 and discuss potential mechanisms of endothelial injury as a key point for the development of lung and distant organ dysfunction, with a focus on direct viral infection and cytokine-mediated injury. Entanglement between inflammation and coagulation and resistance to heparin provide a rationale to consider other therapeutic approaches in order to preserve endothelial function and limit microthrombosis, especially in severe forms. These strategies include nebulized heparin, N-acetylcysteine, plasma exchange and/or fresh frozen plasma, plasma derivatives to increase the level of endogenous anticoagulants (tissue factor pathway inhibitor, activated protein C, thrombomodulin, antithrombin), dipyridamole, complement blockers, different types of stem cells, and extracellular vesicles. An integrated therapy including these drugs has the potential to improve outcomes in COVID-19.